Control of Urochloa decumbens Using Glyphosate Applied by Remotely Piloted Aircraft and Ground Sprayer with Different Spray Nozzles - Luana de Lima Lopes; João Paulo Arantes Rodrigues da Cunha; Quintiliano Siqueira Schroden Nomelini; Cleyton Batista de Alvarenga (Plants, 2024)
The use of remotely piloted aircraft (RPA) to spray pesticides currently occurs, but knowledge about this technology is lacking due to the different locations, targets, and products applied. The objective of this study was to evaluate the control of Urochloa decumbens with glyphosate applied using an RPA (10 L ha−1) equipped with different spray nozzles (XR 11001 and AirMix 11001). For the purpose of comparison, ground application was also performed (100 L ha−1). The deposition was evaluated by means of the quantification of a tracer by spectrophotometry, the droplet spectrum was evaluated with water-sensitive paper, and the control efficiency was evaluated based on visual measurements with percentage scores. Statistical process control was used to analyse the quality of the deposition in the area. The results showed that the application via RPA presented a greater amount of tracer on the leaves than the ground application, suggesting that the former is a good option for application, even providing a lower coverage and number of droplets per area. Both application methods were effective at controlling Urochloa decumbens. The nozzles showed potential for use in applications, with control efficiency higher than 84% from 21 days after application. The percentage of droplets smaller than 100 μm in the applications was less than 5%. No nonrandom behaviour was observed during deposition, indicating a high-quality process.